Dialetics and Structural Organization in the Ẹ̀bìbì Festival Performances of the Ẹ̀pẹ́ People in Lagos State, Nigeria - Babatunde Olanrewaju Adebua; Mobolanle Ebunoluwa Sotunsa (Yoruba Studies Review)
There is growing interest in the study of festivals by literary scholars in African orature. In Nigeria, the festival resources of the Ìjèbú in southwest ̣ - ern Nigeria, specifically the Èbìbì ̣ festival, has been given cursory multi-disciplinary attention in areas such as anthropology, sociology, religions and history. However, scant attention has been paid to the literariness of this corpus of festivals. Moreover, the variety of the festival celebrated by the Èpẹ́ ̣ people in the coastal area of the Ìjẹ̀bú people appears to have been neglected in previous studies of Ìjẹ̀bu festivals. Using salient aspects of literary semiot ́ - ics, this paper explores the Èbìbì ̣ festival of the Èpẹ́ ̣ people by undertaking a literary evaluation of the structural organization, dialetics and interconnectedness of the performances. Observations revealed that levels of structural organization are interconnected to various degrees. Narrative and textual structures are maintained in spite of translations into other languages. Èbìbì ̣ is structured beginning with formulaic exchanges, invocation by the Oluwo and the beating of the sacred Gbẹ̀du drums. Performers sometimes use the formula within a performance to develop oral text. Actions include flogging, as well as acrobatic and gymnastic displays by the performers. The costumes and masks have motifs of riverine animals and fishing accessories. Color codes are symbolically white for cleansing, green for fertility, brown for earth and red for positive energy. The Èbìbì ̣ festival celebrated in Èpẹ́ ̣ is indeed rich in oral 200 Babatunde Olanrewaju Adebua and Mobolanle Ebunoluwa Sotunsa aesthetic forms such as narration, wording, texture and dramatization which enhance its performance aesthetics to a large degree.